ANALISIS KINERJA PERUSAHAAN PERUMDA AIR MINUM AKE GAALE KOTA TERNATE DENGAN PENDEKATAN BALANCE SCORECARD - M. Daffa Imansyah, Noer; Zamzam, Irvan; Hadady, Hartaty (Penerbit Lafadz Jaya, 2025)
The formulation of the problem is how to assess the performance of Perumda Air Minum Ake Gaale Kota Ternate using the balance scorecard (BSC) method. The purpose of the study was to determine the performance of Perumda Air Minum Ake Gaale Kota Ternate using a balance scorecard. This research method uses a quantitative descriptive method. The population in this study were all employees and customers of Perumda Ake Gaale Kota Ternate. The sample was 100 customers and 68 employees. The data collection technique used secondary data and primary data, namely questionnaires. The measurement of the questionnaire used a Likert scale. The data analysis method used in this study was quantitative analysis with a balanced scorecard approach. The results of the study showed that the Balanced Scorecard Assessment Results showed that the company's performance was considered